What makes the difference? Social media platforms and party characteristics as contextual factors for political parties’ use of populist political communication - Magin Melanie; Larsson Anders Olof; Skogerbø Eli; Tønnesen Hedvig (Nordicom Review)
Social media has contributed to the spread of populist political communication, yet we still lack systematic knowledge of the contextual factors affecting its use. In this study, we investigated how and to what degree platforms (Facebook, Instagram, Twitter) and party characteristics (populist vs. non-populist parties; political ideology) affected the use of populist communication by Norwegian political parties on social media during the 2021 national election campaign. Based on a tripartite conceptualisation of populist communication consisting of people-centrism, anti-elitism, and the exclusion of out-groups, we conducted a standardised content analysis of the official social media accounts of nine parties and their party leaders. Populist communication was overall rather rare, being most widespread on Facebook and least widespread on Twitter. Which parties used populist communication the most depended on the platform, and it was not always the populist Progress Party [Fremskrittspartiet] that communicated in the most populist manner. Parties located towards the fringes of the political party spectrum used more populist communication. Anti-elitism was more widespread among left-wing parties, and almost exclusively the right-wing Progress Party excluded out-groups.